" The Role of External Factor in the Democratic Transformation Process (The Arab Spring Countries as a Model) " - Al-Jubori, Sabah Muhammed Saleh (Tikrit Journal For Political Science, 2017)
The democratic transition is often seen through the lens of revolutionary context as the nearly sole pathway in the Arab world. It suggests that there is no room for a democratic transition process without a solution or military intervention (internal or external), revolutions, coups, or protest movements. This is primarily related to the fundamental principle of peaceful power rotation, which has become the core challenge of democratic transition internally, leading to the acceptance of the idea of external interventions and regional influences due to the internal dynamics of Arab political systems.